Interview of Nolan B. Aughenbaugh by Dian O. Belanger - Aughenbaugh, Nolan B. (Byrd Polar Research Center Archival Program, 2005)
Mr. Aughenbaugh, Dr. Nolan Aughenbaugh’s father, pp. 1, 5, 7, 16-17 Admiral Byrd, pp. 2, 8-9 K.B. Woods, pp. 5, 7, 19 Lincoln Washburn, pp. 5 Bill Smith, pp. 6 Bob Frost, pp. 6, 19 Jim Zumberg, pp. 7, 11, 62-63, 67 Larry Gould John Behrendt, pp. 10, 12, 27-28, 44, 46, 48 Hugo Newberg, pp. 10, 12, 19, 29, 48 ________Schuck, pp. 10 Bert Crary, pp. 11, 40, 46-47, 50 Finn Ronne, pp. 11, 15, 20, 22, 24-25, 27, 32, 35, 37, 43-44, 47, 49, 52, 59 Jerry Fierle, pp. 12, 15, 20, 32, 37, 39, 44, 62 John Melville, pp. 13 Paul Walker, pp. 13, 29, 38, 68 Ed Theil, pp. 13, 24, 28, 33, 46,48, 50, 51, 56, 68 Hank Stephens, pp. 23, 31 _______Spears, pp. 29 Admiral Dufek, pp. 32, 36, 41, 47 Commander McCarthy, pp. 32, 37, 49 Cliff Smith, pp. 32 Con Jayberg, pp. 33, 37 ________Somerall, pp. 33 Captain McDonald, pp. 36, 57 ________Beezer, pp. 29 Ernest Shackleton, pp. 40 ________Reedy, pp. 40 Harry Darlington, pp. 45 Jenny Darlington, pp. 45 ________Lassiter, pp. 47 ________Fuchs, pp. 48-49 Sir Edmund Hillary, pp. 48 Dr. George Lano, pp. 54 ________Greedy, pp. 60 ________Haskell, pp. 60 Richard Goldthwait, pp. 63 John Reid, pp. 67 Ralph Kaele, pp. 67 Mario Giovanetto, pp. 67 Harold Heinz, pp. 71 Dr. Aughenbaugh was born in Akron, Ohio. He became interested in the polar regions as a boy. His father told of experiences of traveling by dog sled to determine the feasibility of a railroad to the Artic Ocean. In addition, Nolan saw Admiral Byrd in Akron. After being in the Marines, he attended Purdue University. His advisor arranged for a summer internship on the Greenland Ice Sheet. While a graduate student at the University of Michigan, he had the opportunity to go to the Antarctic. The challenges of the trip are described. Upon arrival, he describes the problems of establishing camp. As an air photo interpreter, Aughenbaugh was permitted to fly over the polar regions. As a surveyor, he helped the Seabees lay out a base. There were tensions between the commander of the military expedition members and the IGY members. Aughenbaugh assisted in taking ice cores. He also did a contour map of a large area around the base. In addition, he was involved in making a traverse. He identified a route through the Grand Chasm to the Dufek Massif. They made seismographs of different areas. Dr. Aughenbaugh had some contact with his parents by use of a ham radio. Upon his return to the United States, the traverse group met at The Ohio State University to write up the results of their study. He later returned to Camp Michigan to study crevasses. After completing his PhD at Purdue, he was hired on as a faculty member. He was later faculty at the University of Missouri, the University of Alaska, and the University of Mississippi. Major Topics Dr. Aughenbaugh’s interest in the Polar Regions Dr. Aughenbaugh’s experiences as a Marine Dr. Aughenbaugh’s experiences in civil engineering, photography, and surveying The challenges of travel and construction in Antarctica The establishment of Ellsworth Station Relationships between military and civilian personnel while stationed in Antarctica Description of the “Phantom Strikes” Traverse preparation and procedure Description of the Grand Chasm and the Dufek Massif Seismological testing Funded by a grant from the National Science Foundation.